Predictive factors for axillary pathological complete response to neoadjuvant therapy in elderly breast cancer patients - Yuying Wang; Rui Wang; Di Lu; Yaling Zeng; Xihui Tu; Shiwei Liu; Purong Zhang (BMC Cancer)
Abstract Purpose This study explores the predictive factors for axillary pathological complete response(apCR) during neoadjuvant therapy(NAT) for elderly breast cancer patients to supplement the indications for retaining the axilla. Methods Comprehensive clinical information was gathered from November 2016 to July 2023 from elderly patients with pathology-confirmed invasive breast cancer who underwent NAT and surgery in the Breast Department of Sichuan Cancer Hospital. The relationships between clinicopathological characteristics and apCR were investigated via retrospective analysis. Univariate analysis of the clinicopathological parameters and efficacy was performed via the chi-square test or Fisher’s exact test, while multivariate analysis was conducted via binary logistic regression. Results This study included 109 elderly patients with breast cancer, with an overall apCR rate of 46.8%. The univariate analysis results showed that the initial clinical lymph nodes negative(cN0) stage, Human Epidermal Growth Factor Receptor 2(HER2) positivity and breast pathological complete response(bpCR) were significantly correlated with high apCR rates(all P < 0.05). Multivariate analysis revealed that apCR exhibited a significant association with initial cN0 stage and HER2 positivity. The apCR rate for HER2-positive elderly patients with initial cN0 disease is 100.0%,whereas the lowest apCR rate is observed in HER2-negative and clinical lymph nodes positive(cN+) patients(36.0%). Subgroup analysis revealed a close relationship between molecular subtypes and apCR. Conclusion This study indicates that initial cN0 stage and HER2 positivity can serve as independent predictive factors for apCR after NAT in elderly breast cancer patients. HER2-positive elderly patients with initial cN0 stage can be considered exempt from axillary lymph node dissection(ALND) after standard NAT.